Upaya Perlindungan Hukum di Indonesia terhadap Anak dan Perempuan Korban Kekerasan Seksual - I Gusti Putu Ery Aditya Purna (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Sexual violence against children and women in Indonesia remains a critical issue with lasting physical, psychological, and social consequences for victims. This study aims to analyze existing legal protection efforts for child and female victims of sexual violence, identify regulatory and implementation weaknesses, and formulate policy recommendations. Employing a normative legal research design with a doctrinal‑descriptive approach, it reviews legislation, scholarly literature, and court decisions. The findings reveal that despite legal frameworks such as Law No. 35/2014 on Child Protection and relevant Criminal Code provisions, significant gaps persist in offense categorization, victims’ access to legal aid services, and inter‑agency coordination. The implications highlight the need for regulatory refinement, strengthened reporting mechanisms, and enhanced capacity of law enforcement and legal aid institutions to ensure comprehensive victim protection.